Diagnosis and study of health and safety at work of timber sector in Sogamoso city (2014)
This paper presents the study carried out in the urban area of Sogamoso, in order to document and obtain a diagnosis of the conditions of health and safety at work of people who develop some activities in the limber industry inthis city . All the processes that art part of the production and processing of wood in this industry in this city. All  the processes that art part of the production and processing of wood in this industry are characterized , identified and evaluated . Bearning in mind the parameters and concepts of occupational health , the necessary information was obtained by the same workers, through a survey, which enabled to capture the creation concerning  socio-economic conditions, working conditions of themselves . Diverse dangers were identified and were assessed the occupational risks existing in each of their productive activities using the GTC 45, 2012. All this allowed defining a series of activies and proposals for improvement, applicable to this type of companies that, if they are welcomed, would mitigate all the shortcomings identified in this research, contribuiting to a better quality of life workers, greater competitiveness and productivity in the timber industry in Sogamoso.